Bourdieu and the Contestation of Religious Authority in the Indonesian Social Media Landscape - Hermansah, Tantan; Fakhruroji, Moch; Muslim, Acep (Universitas Islam Negeri Ar-Raniry, 2026)
This paper investigates the responses of mainstream Islamic mass organizations in Indonesia, NU and Muhammadiyah, to the emergence of Salafi and Wahhabi teachings in the digital realm that challenge their religious authority. Using Bourdieu’s perspective, the restatement of the religious understanding of these two organizations on social media is an attempt to strengthen their established powers in Indonesia while positioning Salafi and Wahhabi groups as newcomers. At the same time, this makes social media a new field in the contestation of religious authority in Indonesia. This study was conducted both online and offline. Online studies were conducted by taking inventory of several websites and discourses that have developed on various internet and social media platforms, while an offline study was conducted through field studies in West Java, Yogyakarta, East Java, and Banten, to investigate the figures and institutions associated with each mass organization, both structurally and culturally. The results show that these organizations have adopted different strategies to address the issue, where NU has reacted defensively, whereas Muhammadiyah has prioritized internal development and charitable activities.